1811 N.H. Laws 74 - (:unkn) unknown (My University, 1811)
An Act To Regulate The Keeping And Selling, And Transporting of Gunpowder, chap. 61, §5: Banned sale or offer for sale of gunpowder in the night time, between sunsetting and sunrising; banned also dealing out any gunpowder at night.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER